Moral Foundations of the Theory of Education in Russian Neo-Kantianism - P. A. Vladimirov; A. V. Lebedeva (Высшее образование в России, 2022)
The article discusses the specificity of constructing pedagogical research within the tradition of Russian Neo-Kantianism. The emphasis is placed on two aspects: 1) philosophy and pedagogy complement each other within the framework of practical philosophy in determining the teleological reason for learning and upbringing, and 2) spiritual and moral foundations determine the efficiency of the process of forming a free and creative individual. The specific features of S.I. Hessen’s concept of moral education in relation to Natorp’s theory of social pedagogy are identified. A comparative analysis of methodological approaches of A.I. Vvedensky and A.V. Veideman to the identification of the purpose of education and upbringing is conducted. The novelty of the study is presented through the actualization of insufficiently studied scientific works of Russian Neo-Kantians, who shared the same field of philosophical discourse with Western European philosophical questions. The relevance of the study is determined by the significance of spiritual and moral values in the context of institutional education. Based on the complex examination as well as the historical and philosophical reconstruction, the general trend of pedagogical research of Russian Neo-Kantians toward the formation of distinct awareness of freedom and its limits is outlined. In the conclusion of the article the authors formulate the statements that have potential for historical and philosophical research, as well as for identification of effective models of correlation of scientific knowledge and spiritual and moral values.